The library as space of cultural mediation and aesthetic education - Adair De Aguilar Neitzel; Cássia Ferri; Adeneri Nogueira de Borba (Arizona State University, 2018)
This research aims at discussing the cultural potency of school and university libraries, and therefore, their contribution to the aesthetic education of users. It is a qualitative research and has as corpus of analysis two libraries in the city of Itajaí, Santa Catarina, Brazil: the Municipal Public and School Library Norberto Cândido Silveira Jr. and the Central and Community Library of the University of Vale do Itajaí. The instruments of data collection were observations recorded in field journals, institutional documents and photographs. The analysis of the data was based on the content analysis procedures, according to Franco (2008). The results indicate that both libraries constitute priority areas for reading and research, and, even with some physical limitations, they explore their spaces to promote coexistence, experience, culture and aesthetic education. Through the analysis, it was possible to identify that the spaces of the libraries point to the trilogy inform, discuss and create, revealing its cultural potency.